The Effect of Using Story Impression Strategy Toward Students’ Reading Comprehension At The Tenth Grade Students’ at SMAN 1 Dua Koto Pasaman - Melia Sasnita; Syahrul Syahrul; Loli Safitri; Eliza Eliza (Jurnal Pendidikan Tambusai, 2022)
There were some students’ problems that the writer found at SMAN 1 Dua Koto Pasaman. First, the students’ problems of reading is lack of knowledge of words meaning and it may influence them understand a good text if there were understanding words. second they got difficult understanding what the text tells about because students’ don’t understand what they have read, they have unable to answer the question of the reading test. This research aims at finding whether there is a significant effect of using the story impression strategy toward students’ reading comprehension, whether the students’ who taught by using story impression strategy and the students who taught without this strategy. The sample was selected by using simple random sampling technique, To analyzed the data, the researcher used the normality by using lilieffors test and homogeneity test by using F test and to rest the hypothesis the researcher used t-test formula and consulted the result into t-table with level significant ?=0.05. The result of the pre-test and post-test scores of experimental and control class, it found that the t-obtained (0,57) was lower than t-table (1.960). Hence, the alternative hypothesis (Ha) was rejeceted. It means that there was no significant effect of using story impression strategy toward students’ reading comprehension. Then, the calculation of post- test both classes: was experimental class and control class, it was obtained that t- obtained was (0,58) was lower than t-table (1.960). Hence, the alternative hypothesis (Ha) was rejected it means that there is no significant difference between used story impression strategy and without used story impression. Then, t-obtained both of classes pretest and posttest is (0,57) it was lower than t- table (1.960). Then, the alternative hypothesis (Ha) was rejeceted. It means that story impression strategy is not better than discovery method in narrative text. Hence, it can be conclude that the experiment research at SMAN 1 Dua Koto Pasaman, the students’ taught by using story impression strategy is not better than students’ with the students who taught without story impression strategy. it means that this strategy does not have a significant effect in improving the reading ability of students in SMA 1 Dua Koto Pasaman.